A motion blur compensation algorithm for 2D DIC measurements of deformable bodies. (21st December 2018) - Lavatelli, A; Turrisi, S; Zappa, E
Abstract: Digital image correlation (DIC) is a widely adopted optical technique to detect motions and deformations dealing with vision-based systems. Considering DIC dynamic applications, motion blur represents one of the most relevant sources of measurement uncertainty. This paper proposes an innovative approach to compensate the effect of motion blur on images coming from deformable bodies, where the amount of blur (w) varies within the single frame. A subset-based technique is developed to estimate and then remove motion blur for each image region. The algorithm is validated both on synthetic images and experimental data, demonstrating its effectiveness at improving the accuracy of the displacements measured by DIC.